Strategi Pengembangan Industri Kecil Gula Aren Di Kecamatan Basidondo Kabupaten Tolitoli - Andhy Saputra; Ramlawati Ramlawati; Hilmi Hilmi (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
Small industry has an important role in absorbing labor, distributing income, and improving community welfare. The problem in this research is how the strategy of developing small palm sugar industry in Basidondo District, Tolitoli Regency. The aim to be achieved in this research is to know the development strategy of small palm sugar industry in Basidondo District, Tolitoli Regency. The population in this study were 107 business units. Sampling in this study using accidental sampling method with a selected sample of 30 respondents. Data analysis was performed using SWOT matrix analysis. The conclusion obtained is based on the SWOT matrix analysis, the strategy that can be done to empower the small palm sugar industry in Basidondo District, Tolitoli Regency is a concentration strategy through horizontal integration. This means that the strategy to be implemented is more defensive, namely avoiding lost sales and lost profits caused by threats. The advice given is to maintain the characteristic taste of the product and improve product quality by creating innovations in product packaging, adding types of products to have high attractiveness in order to remain able to compete with other product.